KESADARAN LINGKUNGAN MASYARAKAT KELURAHAN TUNGGAKJATI TERHADAP DAERAH ALIRAN SUNGAI AGAR MENJADI WARGA NEGARA YANG CERDAS (Studi Kasus: Pendirian Bangunan di Garis Sempadan Sungai Citarum) - Lia Ameliani, - (2021)
The emergence of an environmental problem that occurs on this earth makes humans realize the importance of having environmental awareness along with environmentally conscious behavior. The importance of caring for, managing, and preserving the environment is done so that there is no excessive exploitation and utilization of natural resources that are not in accordance with their original functions carried out by humans on natural resources. enactment of Environmental Law and other regulations such as PUPR Nomor 28 Tahun 2015 Tentang Penetapan Garis Sempadan Sungai dan Garis Sempadan Danau. One of the problems in the river area is the establishment of semi-permanent and permanent buildings just above the border line, this is of course not in accordance with the function of the border line. This is caused by the lack of land to build settlements so that people prefer to build houses above the border and caused by several other factors. In realizing the character of intelligent citizens, the importance of the role of Citizenship Education in increasing environmentally conscious behavior and growing environmental awareness. Keywords: Enviromental awareness, Smart Citizenhsip, Citarum River Border